2019
DOI: 10.1101/671289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prostaglandin EP3 Receptor signaling is required to prevent insulin hypersecretion and metabolic dysfunction in a non-obese mouse model of insulin resistance

Abstract: Objective: Black and Tan Brachyury (BTBR) mice have underlying defects in insulin sensitivity and beta-cell function, even when lean. When homozygous for the Leptin Ob mutation (BTBR-Ob), hyperphagia leads to morbid obesity, and by 10 weeks of age, a type 2 diabetes (T2D) phenotype is fully penetrant. The second messenger molecule, cyclic AMP (cAMP), promotes glucose-stimulated and incretin-potentiated insulin secretion, beta-cell proliferation, and betacell survival. We have previously shown that a key player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(240 reference statements)
0
1
0
Order By: Relevance
“…Additionally, elevated production of prostaglandin E 2 (PE2) and PTGER3 can be targeted to improve insulin secretion from islets [24]. Pathologically, PTGER3 negatively regulates the production of cyclic AMP (cAMP), a potentiator of GSIS [22,25]. Rankin et al [21] showed that agonist (sulprostone) and antagonist of EP3r both significantly reduced GSIS and fasting plasma glucagon in non-human primates with noninsulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elevated production of prostaglandin E 2 (PE2) and PTGER3 can be targeted to improve insulin secretion from islets [24]. Pathologically, PTGER3 negatively regulates the production of cyclic AMP (cAMP), a potentiator of GSIS [22,25]. Rankin et al [21] showed that agonist (sulprostone) and antagonist of EP3r both significantly reduced GSIS and fasting plasma glucagon in non-human primates with noninsulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%